Wideband Self‐Grounded Bow‐Tie Antenna for Thermal MR. (20th February 2020) - Eigentler, Thomas Wilhelm; Winter, Lukas; Han, Haopeng; Oberacker, Eva; Kuehne, Andre; Waiczies, Helmar; Schmitter, Sebastian; Boehmert, Laura; Prinz, Christian; Trefna, Hana Dobsicek; Niendorf, Thoralf
Abstract: The objective of this study was the design, implementation, evaluation and application of a compact wideband self‐grounded bow‐tie (SGBT) radiofrequency (RF) antenna building block that supports anatomical proton ( 1 H) MRI, fluorine ( 19 F) MRI, MR thermometry and broadband thermal intervention integrated in a whole‐body 7.0 T system. Design considerations and optimizations were conducted with numerical electromagnetic field (EMF) simulations to facilitate a broadband thermal intervention frequency of the RF antenna building block. RF transmission (B1 + ) field efficiency and specific absorption rate (SAR) were obtained in a phantom, and the thigh of human voxel models (Ella, Duke) for 1 H and 19 F MRI at 7.0 T. B1 + efficiency simulations were validated with actual flip‐angle imaging measurements. The feasibility of thermal intervention was examined by temperature simulations (f = 300, 400 and 500 MHz) in a phantom. The RF heating intervention (Pin = 100 W, t = 120 seconds) was validated experimentally using the proton resonance shift method and fiberoptic probes for temperature monitoring. The applicability of the SGBT RF antenna building block for in vivo 1 H and 19 F MRI was demonstrated for the thigh and forearm of a healthy volunteer. The SGBT RF antenna building block facilitated 19 F and 1 H MRI at 7.0 T as well as broadband thermal intervention (234‐561 MHz). For the thigh of the human voxel models, a B1 + efficiency ≥11.8 μT/√kW was achieved at a depth of 50 mm. Temperature simulations and heating experiments in a phantom demonstrated a temperature increase ΔT >7 K at a depth of 10 mm. The compact SGBT antenna building block provides technology for the design of integrated high‐density RF applicators and for the study of the role of temperature in (patho‐) physiological processes by adding a thermal intervention dimension to an MRI device (Thermal MR). Abstract : The objective of this study was the design, implementation, evaluation and application of a compact wideband self‐grounded bow‐tie (SGBT) radiofrequency (RF) antenna building block that supports anatomical proton ( 1 H) MRI, fluorine ( 19 F) MRI, MR thermometry and broadband thermal intervention integrated in a whole‐body 7.0 T system. The compact SGBT antenna building block provides technology for the design of integrated high‐density RF applicators and for the study of the role of temperature in (patho‐) physiological processes by adding a thermal intervention dimension to an MRI device.